Perioperative SARS-CoV-2 Infection in Patients Undergoing Elective Surgery in Gynecology Clinic: Tertiary Center Experience - Reyhan Toptas, Gulnihal; Unlubilgin, Eylem; Kinay, Tugba; Dogan, Ali Riza; Akgul, Mehmet Akif; Aslanova, Sitare; Ercan, Emel Ebru; Korkmaz, Vakkas; Erturk Aksakal, Sezin; Ustun, Yaprak (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: The objective of this study was to determine the incidence of perioperative “severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)” infection among women, operated during Coronavirus disease-2019 (COVID-19) era. STUDY DESIGN: All patients who were operated on between March 11, 2020, and December 31, 2020, in our gynecology clinic were included in this cross-sectional study. The clinical and demographic characteristics of the patients, preoperative and postoperative SARS-CoV-2 positivity, the progress of the infection, and the survival rates in positive cases were analyzed. COVID-19 cases were diagnosed by reverse transcription-polymerase chain reaction testing for SARS-CoV-2. RESULTS: Operations of 133 (33%) of 406 patients were canceled for various reasons. 275 patients were operated on. Preoperatively three patients were diagnosed with COVID-19. One of these patients died and two were operated on after treatment and self-isolation. Only one (0.4%) patient was diagnosed with COVID-19 30 days postoperatively and completely recovered. We calculated the perioperative SARS-CoV-2 positivity rate as 1.4% (276 surgeries were planned and 4 patients were diagnosed with COVID-19). During the study, 107 physicians worked in our clinic alternately. Two (1.8%) of these physicians were diagnosed with COVID-19 and completely recovered without the need for intensive care. In addition, nine patients who were previously diagnosed with COVID-19 were operated on. Postoperative respiratory and other system complications did not occur in nine patients, previously diagnosed with COVID-19. CONCLUSION: The results of our study show that gynecological surgical procedures do not increase the transmission and mortality rates of SARS-CoV-2 among patients and healthcare professionals as long as infection control measures are followed.